The first approved drug for abnormal bone formation: palovarotene challenges and way forward - Alizai, Hassam Nasir Khan; Pasha, Aainah; Alizai, Parsa Khan; Zia, Namra (Journal of the Pakistan Medical Association, 2025)
The current communication was planned to assess the validity of a potential cure for two disorders of bone formation that have traditionally been limited to symptomatic treatment in orthopaedic medicine. Heterotopic ossification and fibrodysplasia ossificans progressive, also known as Stoneman Syndrome, are rare conditions that result in abnormal bone formation within soft tissues, causing immense suffering and high mortality rate due to limited treatment options. Several studies have supported the promising outcomes associated with palovarotene, a novel drug, in terms of reducing lesion volumes induced by heterotopic ossification, alleviating inflammation and pain and doing so with minimal side effects. Given its novelty, research on palovarotene is still in its infancy. Consequently, challenges surrounding the introduction of palovarotene needs to be studied along with its potential indications and advantages in the disorders characterised by abnormal bone formation. Key Words: Palovarotene, Myositis ossificans, Bone morphogenetic proteins.